Public expenditures for agricultural and rural development in Africa - Tewodaj Mogues; Benin, S. (Samuel) (London ; New York : Routledge, 2012)
"The Minister of Finance of an African country needs to reallocate the country's public investment to help achieve the Millennium Development Goals (MDGs) of halving the proportion of the poor and hungry by 2015: Should the minister increase investment in health and education, with the view that a future productive labour force can lift itself out of poverty? Or shift a greater share of the public budget to support agricultural productivity directly, as the vast majority of the poor relies on agriculture as their main livelihood? Or yet, should the minister focus more on building roads in rural areas where most of the poor live, to enable both people and goods to move more cheaply and thus boost the functioning of markets? These questions highlight some of the challenges that many African countries (and indeed much of the developing world) face in supporting agricultural and rural growth and reducing poverty. The book brings together recent analysis on the trends in, and returns to, public spending for agricultural growth and rural development in Africa. Case studies of selected African countries provide insights into the contributions of different types of public expenditures for poverty, growth and welfare outcomes, as well as insights into the constraints in gaining development mileage from investments in the agricultural sector. This work will be of interest primarily to analysts, researchers and students interested in agricultural and rural development and poverty in Africa and other developing regions, as well as to African policymakers, donor agencies, and civil society organisations concerned with these issues"--
Includes bibliographical references (p. [263]-275) and index.
Keywords: Government spending policy -- Africa -- Case studies; Agricultural development projects -- Africa -- Case studies; Rural development -- Africa -- Case studies; Economic assistance, Domestic -- Africa -- Case studies; Africa -- Appropriations and expenditures -- Case studies